Mediterranean quarantines, 1750-1914 space, identity and power - Chircop, John; Martinez, Francisco Javier (Social histories of medicine., 2018)
Mediterranean quarantines investigates how quarantine, the centuries-old practice of collective defence against epidemics, experienced significant transformations from the eighteenth century in the Mediterranean Sea, its original birthplace. The new epidemics of cholera and the development of bacteriology and hygiene, European colonial expansion, the intensification of commercial interchanges, the technological revolution in maritime and land transportation and the modernisation policies in Islamic countries were among the main factors behind such transformations. The book focuses on case studies on the European and Islamic shores of the Mediterranean showing the multidimensional nature of quarantine, the intimate links that sanitary administrations and institutions had with the territorial organisation of states, international trade, the construction of national, colonial, religious and professional identities of political regimes.